Thermal fluctuations, QNMs, and emission energy of charged ADS black hole with nonlinear electrodynamics - Javed, Faisal; Basit, Abdul; Caliskan, Aylin; Güdekli, Ertan (Frontiers in Astronomy and Space Sciences, 2023)
This study examines the thermodynamics of charged anti-de Sitter (AdS) black holes (BHs) with nonlinear electrodynamics (NED) using quasinormal modes (QNMs) and thermal fluctuations. For this purpose, we calculate the Hawking temperature and discuss the stable configuration of the considered black hole using heat capacity. First, we study the interesting aspects of the emission of energy. Then, we explore the effects of thermal corrections on thermodynamic quantities and their corrected energies. We study the phase transitions of the system in the background of thermal fluctuations. It is concluded that the presence of a coupling constant enhances the thermodynamically stable configuration of uncharged and charged AdS BH geometries. We highlight that our results are in good agreement with the thermodynamics of the previous black hole solutions and assumptions presented in the literature.